2011
DOI: 10.1038/cgt.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mesothelioma with gene-modified PA1STK cells and ganciclovir: a phase I study

Abstract: Mesothelioma is an incurable cancer of the pleura with a life expectancy of less than 1 year. On the basis of in vivo efficacy seen with the herpes simplex virus type 1 thymidine kinase (HSVtk) suicide gene-modified PA1STK cell line and ganciclovir (GCV) in a murine model of mesothelioma, a first in humans, clinical trial was designed for this therapeutic concept. The study was a phase I clinical trial using direct infusion of escalating doses of HSVtk suicide gene-modified PA1STK cells directly into tumor-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The earliest intrapleural cellular immunotherapies involved the delivery of genetically modified allogeneic ovarian carcinoma cells engineered to express the herpes simplex virus thymidine kinase gene (HSVtk) in combination with systemic ganciclovir (gene‐modified PA1‐STK cells) . While not initially designed to be an immunotherapy protocol per se, the generation of antitumor immune responses has been determined to be a key mechanism of action of intrapleural gene‐modified PA1‐STK cells . Induced immune responses may have developed against mesothelin, which is present on both the cell surfaces of the gene‐modified PA1‐STK cells and MPM cells within the involved pleural space.…”
Section: Intrapleural Cellular Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest intrapleural cellular immunotherapies involved the delivery of genetically modified allogeneic ovarian carcinoma cells engineered to express the herpes simplex virus thymidine kinase gene (HSVtk) in combination with systemic ganciclovir (gene‐modified PA1‐STK cells) . While not initially designed to be an immunotherapy protocol per se, the generation of antitumor immune responses has been determined to be a key mechanism of action of intrapleural gene‐modified PA1‐STK cells . Induced immune responses may have developed against mesothelin, which is present on both the cell surfaces of the gene‐modified PA1‐STK cells and MPM cells within the involved pleural space.…”
Section: Intrapleural Cellular Immunotherapymentioning
confidence: 99%
“…Induced immune responses may have developed against mesothelin, which is present on both the cell surfaces of the gene‐modified PA1‐STK cells and MPM cells within the involved pleural space. In a phase I clinical trial of intrapleural delivery of gene‐modified PA1‐STK cells followed by 7 days of intravenous ganciclovir infusion in MPM, treatment was overall well tolerated and robust increases in pleural and serum Th1 and Th2 cytokines after treatment were observed …”
Section: Intrapleural Cellular Immunotherapymentioning
confidence: 99%
“…In the presence of ganciclovir, CCL5-HSV-TK engineered MSCs led not only to a significant reduction in the growth of primary pancreatic tumors, but also dramatically reduced the incidence of metastases [49]. A direct comparison of the Tie2 and CCL5 targeting strategies in an orthotopic model of hepatocellular carcinoma showed that while both approaches suppress tumor growth, the CCL5 strategy was more effective [50]. We believe that based on the unique biology of each tumor type, each tumor entity will be more or less susceptible to a specific targeting approach.…”
Section: Tissue Specific Promoters Allow Selective Delivery Of Therapmentioning
confidence: 99%
“…Based on these studies, a cell-transfer trial was conducted by Schwarzenberger et al [61] at the Louisiana State University (LSU) Medical Center in New Orleans. The study was a phase I clinical trial involving direct IP infusion of escalating doses of HSVtk suicide gene-modified PA1STK cells in 15 patients with MM followed by 7 days of intravenous GCV.…”
Section: Vectors Used In Pleural Gene Therapymentioning
confidence: 99%
“…No significant differences were seen between serum and pleura cytokine profiles, with the exception of IL-10, which was consistently elevated in the pleural fluid specimens. No objective radiographic responses were observed in any of the treated patients [61]. …”
Section: Vectors Used In Pleural Gene Therapymentioning
confidence: 99%